Analisis Peran Manfaat dan Kemudahan dalam Minat Penggunaan Mobile Banking Syariah - Arifah, Nur; Ratno, Fernaldi Anggadha (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
This study aims to analyze the influence of benefits and convenience on interest in using sharia mobile banking with attitude as an intervening variable in UIN Salatiga students. This research is quantitative research, this research uses primary data obtained through questionnaires. The population of this study were UIN Salatiga students, the sampling technique in this study used purposive sampling. The sample obtained was 97 respondents. The data was processed using the statistical software program for social sciences (SPSS) version 25. The results of this study show that the influence of benefits, convenience and attitude has a positive and significant effect on interest in using sharia mobile banking, the influence variable of benefits and convenience has a positive and significant effect on attitudes, and The results of the path analysis test for attitude variables can mediate the influence of benefits and convenience on interest in using sharia mobile banking.